2012
DOI: 10.1111/j.1525-1470.2011.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Spitz Nevus Arising upon a Congenital Glomuvenous Malformation

Abstract: There are several reports of the collision of vascular and pigmentary anomalies (e.g., phakomatosis pigmentovascularis) and the association between congenital melanocytic nevi and infantile hemangiomas. We report a case of Spitz nevus arising in skin overlying a congenital plaque-like glomuvenous malformation (GVM). This is the first report of a Spitz nevus arising in direct contiguity to a GVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…However, the malformation was located in the deep dermis and it did not intermingle with the nevus. 7 In the report by Wu et al, 3 the authors concluded that the association of infantile hemangioma and congenital melanocytic nevi described in their cases was "real and not coincidental," and they hypothesized regarding the role played by defects in regulatory pathways which would be common to the tissues affected in both birthmarks. This report was conducted before the introduction in literature to the concept of perivascular migration of melanocytic tumoral cells, a concept mainly developed by Barnhill et al 9,10 According to this concept, tumoral melanocytic cells migrate along vessels and other tracks in parallel to the migration of embryonic stem cells from the neural crest.…”
Section: Discussionmentioning
confidence: 95%
“…However, the malformation was located in the deep dermis and it did not intermingle with the nevus. 7 In the report by Wu et al, 3 the authors concluded that the association of infantile hemangioma and congenital melanocytic nevi described in their cases was "real and not coincidental," and they hypothesized regarding the role played by defects in regulatory pathways which would be common to the tissues affected in both birthmarks. This report was conducted before the introduction in literature to the concept of perivascular migration of melanocytic tumoral cells, a concept mainly developed by Barnhill et al 9,10 According to this concept, tumoral melanocytic cells migrate along vessels and other tracks in parallel to the migration of embryonic stem cells from the neural crest.…”
Section: Discussionmentioning
confidence: 95%
“…Рідко ці клітини можуть бути клітинним субстратом трьох типів гломусних пухлин, класифікованих на основі їх домінуючого компонента: тверді (переважно гломусні клітини), гломангіома (переважно кровоносні судини), гломангіоміома (переважно гладком'язові клітини). Описаний випадок невуса Шпіца, який виник на шкірі над вродженою ГВМ [2], більшість гломусних пухлин є доброякісними, хоча також повідомлялося про злоякісні випадки [10,17], що вимагає посиленої діагностики при підозрі на ГВМ, особливо при нехарактерній клінічній картині [21].…”
Section: матеріали та методиunclassified